Genres as Social Affect: Cultivating Moods and Emotions through Playlists on Spotify - Siles González, Ignacio (2019)
This article bridges work on media technologies and affect theories through an analysis of how users appropriate playlists on Spotify. Our study draws on 30 interviews with users of music streaming services in Costa Rica and an analysis of their accounts on these platforms. We discuss how users create playlists as a means to cultivate affect. The notion of cultivation stresses the dynamic and ritual work involved in producing, capturing, and exploring moods and emotions. We argue that playlists work as “genres”—fusions of musical substance, sociotechnological assemblages, and sociomaterial practices—to respond to the exigencies of affect. This helps turning the platform into an obligatory intermediary in the establishment of a utilitarian relationship between users and music. We draw on Berlant’s notion of “intimate public” to analyze how playlists form the basis of collective experiences that serve Spotify’s political-economic project. As material embodiments of cultivated affect, playlists offer a promise of identification and belonging to “intimate publics” formed by strangers through the specific bonds between music, technology, and affect they enact (as genres). Our analysis concludes with a discussion of the implications of our study for rethinking the relationship between technology, affect, and genre.